Performance Evaluation of T-Beam Bridge Girder: A Structural Capacity Analysis for Flexure and Shear - Fetriani, Wenti; Naduta, Oktiardi; Putra, Bery Aristha; Dewi, Sari Utama (Jurnal Teknik Sipil, 2026)
T-beam girders are primary load-bearing elements in short- to medium-span reinforced concrete bridges, requiring accurate assessment of flexural and shear capacities to satisfy ultimate limit state criteria. This study evaluates the structural performance of a 12 m span reinforced concrete T-beam bridge through deterministic analysis in accordance with SNI 2847:2019 and load provisions specified in SNI 1725:2016. Unlike studies relying on numerical simulation or simplified checks, this research employs a code-consistent analytical comparison of demand and capacity to verify structural adequacy under the governing load combinations. Ultimate bending moments (Mu) and shear forces (Vu) were calculated based on bridge geometry, material properties, and reinforcement detailing, and subsequently compared with factored flexural (ϕMn) and shear (ϕVn) capacities. The results indicate that the maximum Mu of 1,775.93 kNm and Vu of 623.76 kN remain below their respective capacities, with ϕMn equal to 1,795.93 kNm and ϕVn exceeding Vu. These findings confirm that the T-beam girder satisfies ultimate limit state requirements and demonstrate the effectiveness of deterministic code-based evaluation for bridge safety verification.